Focusing and calming games for children : mindfulness strategies and activities to help children relax, concentrate and take control - Plummer, Deborah (Jessica Kingsley Publishers, 2012)
"Having the ability to focus, relax and concentrate is key to enabling children and young people to achieve emotional well-being, and is also important for a child's development of skills and abilities. This book uses a model of 'mindfulness play' to help children to achieve well-being, an approach designed by the author which encourages children to build awareness of their inner and outer worlds"--Publisher's description.